Encyclopaedia of women health and empowerment -1 New born girl child Gender prejudices, healthcare and development - Ganguly, N. K.; Kumar, Meenal; Kumar, R. (New Delhi Deep & Deep Publications, 2009)
Female babies are vulnerable : let them not perish